2014
DOI: 10.5527/wjn.v3.i4.256
|View full text |Cite
|
Sign up to set email alerts
|

From crystalluria to kidney stones, some physicochemical aspects of calcium nephrolithiasis

Abstract: Nephrolithiasis seems to be the result of crystal formation, aggregation and retention in the kidney during crystalluria. These processes have to occur within the short urinary transit time through the kidney being in the order of few minutes. Recently much work was done on rather qualitative aspects of nephrolithiasis like genetics, metabolism and morphology. In this review we try to provide some quantitative information on urinary supersaturation with respect to stone minerals, especially Ca oxalate (CaOx), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 52 publications
(75 reference statements)
0
31
0
1
Order By: Relevance
“…Bauman and co-workers (2014) have even queried the role of crystalluria [12]. They comment that the factors which finally determine whether crystalluria provokes stone formation or whether it is a useful mechanism to eliminate heavy soluble substances with minimum water loss remains open to further research [12]. Thus, considerable uncertainty exists about the mechanisms of stone formation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Bauman and co-workers (2014) have even queried the role of crystalluria [12]. They comment that the factors which finally determine whether crystalluria provokes stone formation or whether it is a useful mechanism to eliminate heavy soluble substances with minimum water loss remains open to further research [12]. Thus, considerable uncertainty exists about the mechanisms of stone formation.…”
Section: Discussionmentioning
confidence: 96%
“…More recently, Ratkalkar (2011) observed that despite the current understanding of the physical chemistry of stone formation, no single abnormality has served to distinguish stone formers from normal individuals and many SFs have no identifiable abnormality that explains the propensity of their urine to nucleate stone constituents at lower levels of SS, to support accelerate growth of the crystals formed, or to permit crystals to adhere to each other (aggregate) or to some intrarenal structure [46]. Bauman and co-workers (2014) have even queried the role of crystalluria [12]. They comment that the factors which finally determine whether crystalluria provokes stone formation or whether it is a useful mechanism to eliminate heavy soluble substances with minimum water loss remains open to further research [12].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In filtered urine, this FP was found to be very high. It exceeded about 14 times the product of ion activities (Ca e × Ox e ) observed in urine after equilibration with CaOx crystals in excess, the ratio Ca a × Ox a /Ca e × Ox e being a measure for the state of saturation [2]. Ion activities and thus crystallization tendency of calcium and oxalic acid are reduced by the formation of highly soluble complexes of Ca with citric acid and of Ox with magnesium.…”
Section: Crystallization Conditions Of Caox In Urine and Within The Kmentioning
confidence: 93%
“…Fourier transform infrared spectroscopy being now commonplace for stone analysis shows that calcium oxalate (CaOx) is the most frequent stone compound. For calcium nephrolithiasis, the most frequent stone disease and the topic of this chapter, the important substances are calcium, oxalic and citric acid the latter being a calcium chelator [2]. However, not all stone formers show a pathological excretion of these compounds, and some anomalies also are found in urine of people without stone formation.…”
Section: Introductionmentioning
confidence: 98%